Cobalamin status in sickle cell disease. Issue 1 (26th July 2012) - Ajayi, O. I.; Bwayo‐Weaver, S.; Chirla, S.; Serlemitsos‐Day, M.; Daniel, M.; Nouraie, M.; Edwards, K.; Castro, O.; Lombardo, F.; Gordeuk, V. R.
Summary Introduction Some studies comparing serum cobalamin in individuals with and without sickle cell disease (SCD) have suggested a higher prevalence of cobalamin deficiency in SCD but others have not. Our aim was to prospectively compare cobalamin status in African–Americans with and without SCD. Methods We analyzed blood samples from 86 subjects in two groups: SCD (n = 29) and non‐SCD (n = 57). Serum cobalamin, folate, homocysteine, methylmalonic acid (MMA), anti‐intrinsic factor antibody, Helicobacter pylori antibody, and gastrin were measured and compared. Results The median cobalamin was 235 pm in the SCD group vs. 292 pm in the non‐SCD group (P‐value = 0.014). No significant differences in MMA or homocysteine were seen. Using the criteria of a low cobalamin and an elevated MMA or an elevated MMA alone, cobalamin deficiency was suggested in 4 (13.8%) in the SCD group and 6 (10.5%) in the non‐SCD group. Two of these SCD patients and four of these control subjects had chronic renal disease, which may lead to elevated MMA in the absence of cobalamin deficiency. The remaining four met criteria for cobalamin deficiency, 2 (6.9%) in the SCD group and 2 (3.5%) in the non‐SCD group (P = 0.6). Conclusion A lower cobalamin was observed in SCD patients without a higher prevalence of cobalamin deficiency. The inclusion of haptocorrin and holotranscobalamin measurement in future studies may provide a better assessment of cobalamin status in this patient group.